Domestic homicide: interviews with families, survivors and professionals and analysis of domestic homicide reviews, 2019-2022 - Chantler, Khatidja (UK Data Service, 2022)
This three-year ESCR-funded project aimed to address important gaps in knowledge of domestic homicide. Domestic homicide is both a global and a domestic problem that disproportionately affects women. Domestic Homicide Reviews (DHRs) were introduced as a statutory requirement in England and Wales in 2011 to review the circumstances in which the death of a person aged 16 or over has, or appears to have, resulted from violence, abuse or neglect perpetrated by an intimate ex/partner, relative, or member of the same household (Home Office, 2016). The project aimed to learn from the experiences of families who had lost a relative to domestic homicide; victims/survivors of domestic abuse; professionals, and domestic homicide reviews (DHRs) to document, analyse, map, and influence policy and practice to prevent future domestic homicides. To this end the research team conducted a systematic review of domestic homicide reviews internationally to build knowledge about their focus, organisation and lessons identified in order to inform future developments of DHRs; analysed all publicly available DHRs to identify possible risk and contextual factors preceding the homicides and the recommendations made in DHRs to prevent future domestic homicides, and, explored the journeys of victim/survivors, families and agencies in relation to high risk domestic violence and domestic homicide to ensure policy and practice is cognisant of and learns from their experiences and to investigate good practice, lost opportunities for interventions and to identify areas for strengthening responses for the prevention of domestic homicides. The total archived dataset comprises quantitative and qualitative data: 1) an SPSS database containing data from the 302 DHRs. 2) The interview transcripts with family members (n=7) who had been bereaved by domestic homicide and survivors of domestic violence (n=10) and nineteen semi-structured, audio recorded interviews (9 in Wales, 10 in Lancashire) conducted with professionals who have worked with victims or been involved in DHRs, e.g. healthcare professionals, social workers, voluntary agency staff, police officers from the two identified CSP networks (Lancashire and Wales). These are also available in the form of three digital films here: https://domestichomicide-halt.co.uk/resource-center/. Learning from Domestic Homicide Reviews using Experience Based Co-Design, also known as Homicide Abuse Learning Together (HALT) was a three-year study funded by the Economic and Social Research Council (ES/S005471/2) and carried out by researchers at Manchester Metropolitan University, the University of Central Lancashire and Liverpool John Moores University. The key aim was to enhance policy and practice by improving methods for implementing the recommendations of domestic homicide reviews. Domestic homicide is both a global and a domestic problem. Domestic Homicide Reviews (DHRs) were introduced as a statutory requirement in England and Wales in 2011 to review the circumstances in which the death of a person aged 16 or over has, or appears to have, resulted from violence, abuse or neglect perpetrated by an intimate ex/partner, relative, or member of the same household (Home Office, 2016). The HALT project aimed to address important gaps in knowledge of domestic homicide and to learn from the experiences of families who had lost a relative to domestic homicide; victims/survivors of domestic abuse; professionals, and domestic homicide reviews (DHRs) to document, analyse, map, and influence policy and practice to prevent future domestic homicides. From our findings, we developed key themes that generated outputs including policy briefings, a series of films, a book of poetry based on the transcripts of survivor and family interviews. These are available at the resources page of the HALT project website here: https://domestichomicide-halt.co.uk/resource-center/